THE QUR'AN'S CONTRIBUTION TO THE DEVELOPMENT OF MATHEMATICS IN THE HISTORY OF ISLAMIC CIVILIZATION - Andrianto, Dedi; Al Ayyubi, Ibnu Imam; Nawawi, M. Latif; Hilmansah, Deden; Bin Ahmad al-Jafari, Syed Muhammad Adib Termizi (Jazirah: Jurnal Peradaban dan Kebudayaan, 2025)
This study explores the contribution of the Qur'an to the development of mathematics in the history of Islamic civilization, particularly during the Golden Age of Islam (8th to 14th centuries CE). The Qur'an served as a source of inspiration for Muslim scholars in advancing mathematics through spiritual and philosophical values, such as hisab (calculation), mizan (balance), and the orderliness of nature. This research employs a historical-thematic approach by analyzing Qur'anic verses and the scientific works of prominent figures such as Al-Khwarizmi, Al-Biruni, and Ibn Sina. The findings reveal that the teachings of the Qur'an encouraged innovations and advancements in mathematics that were not only technical but also spiritually oriented. This contribution played a significant role in laying the foundation for modern mathematics and providing an intellectual legacy to global civilization.